Efficacy and Safety of Rotigotine Transdermal Patch on Neuropsychiatric Symptoms of Parkinson's Disease: An Updated Meta-Analysis and Systematic Review - Yan, Junqiang; Ma, Hongxia; Liu, Anran; Huang, Jiarui; Wu, Jiannan; Yang, Jianxue (Frontiers in Neurology, 2021)
Objective: The effects of rotigotine transdermal patch (RTG) on neuropsychiatric symptoms of Parkinson's disease (PD) outcomes remain controversial, the aim of this review was to determine the efficacy and safety of RTG on neuropsychiatric symptoms of PD. Methods:In this systematic review and meta-analysis, PubMed, Cochrane Library, EMBASE and Web of science were searched until May 10, 2021 for RCT comparing RTG and placebo in PD.We analyzed the data using Review Manager 5. 2 software. The quality of evidence was assessed using the grading of recommendations assessment,development, and evaluation approach (GRADE). In order to avoid false positive results caused by random errors, we use TSA software for trial sequential analysis (TSA). Results: We included 10 studies（1844 patients）. The meta-analysis showed that compared with placebo, RTG can significantly improve scores for Apathy Scale ( MD= -1. 68, 95% confidence interval [CI]: -2.74 to -0.62, P = 0.002; moderate certainty), Beck Depression Inventory-II (MD=-1.19, 95% CI: -2.26 to -0.11, P = 0. 03; moderate certainty), the Non-Motor Symptoms Scale (MD = -3. 66, 95% CI: -4. 30 to -3.01, P ＜ 0.00001; moderate certainty), the sleep/fatigue domains of NMSS ( MD=-2.03,95%CI:-3.08 to -0. 98, P = 0.0001; moderate certainty), the mood/apathy domains of the Non-Motor Symptoms Scale (MD=-2.48, 95% CI: -4.07 to -0.89, P = 0.002; high certainty), the 8-item Parkinson’s disease Questionnaire ( MD = -4. 93, 95% CI:-6.79 to -3.07, P ＜ 0. 00001; moderate certainty) and the 39-item Parkinson’s disease Questionnair (MD=-3.52, 95% CI:-5.25 to -1.79, P＜0. 0001; high certainty). However, there was no statistically significant difference on Snaith-Hamilton Pleasure Scale（MD=-0.12, 95% CI:-0.58 to 0.34, P = 0.61）. Our results showed that RTG exerts a positive effect on sleep. According to TSA, results implied that except for Beck Depression Inventory-II (BDI-II), conclusive evidence have been obtained in RTG group. And it has been proved in our meta-analysis that rotigotine has a good safety and tolerability. Conclusions: RTG can effectively improve neuropsychiatric symptoms, sleep quality and quality of life in patients with PD, and further trials may not be required.